2005
DOI: 10.1080/10739680500253402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glucose Control and Improvement of Insulin Resistance on Microvascular Blood Flow and Endothelial Function in Patients with Diabetes Mellitus Type 2

Abstract: Improving metabolic control has beneficial effects in microvascular function in type 2 diabetic patients. Treatment of type 2 diabetic patients with pioglitazone exerts additional effects on endothelial function beyond metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 50 publications
1
25
1
Order By: Relevance
“…[26][27][28][29][30][31][32] Retinal vasculature is morphologically and functionally related to cerebral vessels because of their common origin from the internal carotid artery. An increased arterial retinal WLR has been described in patients with a history of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] Retinal vasculature is morphologically and functionally related to cerebral vessels because of their common origin from the internal carotid artery. An increased arterial retinal WLR has been described in patients with a history of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Given the high prevalence of diabetes mellitus in patients with PAD, it is interesting to note that studies have also suggested that pioglitazone could improve vascular function. [84][85][86] The relevance of these changes to functional status in patients with PAD remains unknown.…”
Section: Endothelial and Microcirculatory Dysfunctionmentioning
confidence: 99%
“…The thiazolidinediones favorably affect peripheral and coronary endothelial dysfunction [37][38][39] and modestly improve blood pressure. 40 Proposed mechanisms for these effects include improved endothelium-dependent vasodilation via restoration of insulin-dependent endothelial nitric oxide release 41 and improved vasomotor tone via increased expression of vascular endothelial growth factor and reduced expression of endothelin-1.…”
Section: Endothelial Function and Hypertensionmentioning
confidence: 99%